UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS I SD NEGERI 43 LUBUKLINGGAU PADA MATERI BANGUN DATAR DENGAN PEMBELAJARAN DARING - Nelly Rosmiati (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the increase in the learning outcomes of first grade students at SD Negeri 43 Lubuklinggau on the flat-shaped material with online learning. This research is a classroom action research (CAR) referring to the Kemmis and Mc. Taggart which includes action planning, action implementation and observation, and reflection. Based on the results of the implementation of classroom action research that has been carried out 1) Online learning can improve student learning outcomes about Bangun Datar, this increase can be seen from student learning outcomes in pre-cycle 4 students complete (21.05%) increasing in cycle 1 to 11 students complete ( 57.89%) and in cycle 2 managed to increase to 17 students completed (89.47%). 2) Online learning can also increase student activity and involvement in the learning process. This can be seen from the active involvement of students in the pre-cycle only 4 active students (21.05%), increased in cycle 1 to 11 students (57.89%) active and in cycle 2 managed to increase to 17 students (89.47%) active.